(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The purpose of this research is to experimentally identify the performance of most of the light-weight observation towers open for public in Latvia. It analyzes the structure of towers, technical condition, dynamic parameters and dynamic response to human movement along the tower height. During the experiment there were measured and recorded the vibration accelerations of 18 observation towers’ upper platform. Further dynamic parameters were extracted using the spectral analysis. There was performed the sensitivity analysis to establish parameters that most influences the dynamic response amplitudes due to human movement. All experimentally obtained fundamental frequencies of the inspected towers are in the typical range of human walking frequencies. It is found that the main parameter that denotes the response level (acceleration amplitude) of the tower due to human movement is a tower self-weight.